On disturbance rejection control for nonlinear three‐revolute prismatic spherical ball and plate systems. Issue 2 (4th May 2021) - Cai, Tao; Dong, Zhenye; Liu, Xinning
Abstract: The three‐revolute prismatic spherical ball and plate system (BP) is a typical complex nonlinear uncertain system involving axial coupling, friction, and other nonlinear factors. It is difficult to identify the model for each factor and isolate its effect from other factors. In addition to such challenge, the measurement noise, which is beyond the capability of many traditional closed‐loop control methods, exists in the system. For this reason, an active disturbance‐rejection control scheme combining linear tracking differentiator is presented to tackle the problems in the BP system. The simulation and real system test are conducted in response to point‐to‐point trajectories, circular and rectangular loci. The results demonstrate that fast response with small steady error can be achieved by the proposed control method. GTOC:The paper provide an active disturbance‐rejection control scheme combining linear tracking differentiator for the BP system control, The simulation and real system test demonstrate that fast response with small steady error can be achieved by the proposed control method.